The hemostatic activity of Manilkara zapota (L.) P. Royen latex associated with fibrinogenolytic activity - Kusuma, C G; Gubbiveeranna, Vinod; Sumachirayu, C K; Bhavana, S; Ravikumar, H; Nagaraju, S (Plant Science Today, 2020)
Manilkara zapota (L.) P. Royen (Sapotaceae), is widely used in traditional medicine for various ailments like, diarrhea, pulmonary diseases, piles, ulcers and to treat wounds. The present study evaluates the role of M. zapota latex in hemostasis. The processed latex named as M. zapota natant latex (MzNL), has proteins at the concentration of 8 mg/ml and showed protein bands in Sodium dodecyl sulfate-polyacrylamide gel electrophoresis (SDS-PAGE). The proteolytic activity of MzNL was evaluated using casein in comparison with trypsin. The phenylmethylsulfonyl fluoride (PMSF) inhibited the protease activity indicating the possible presence of serine protease. The effect of temperature, pH and metal ions on proteolytic activity was evaluated. MzNL exhibited fibrinogenolytic activity by hydrolysing A? and B? subunits of fibrinogen. However, ? subunit remained resistant for hydrolysis. MzNL hydrolyzed all the subunits of collagen type I and IV at the concentration of 8 µg and 25 µg in 20 µl each respectively. MzNL showed procoagulant activity and is devoid of hemolytic activity. Fibrinogenolytic activity and procoagulant nature of MzNL suggests its possible role in blood coagulation that in turn restores hemostasis.